Peran Moderasi Komite Audit dalam Hubungan Audit Tenure dan Reputasi KAP dengan Kualitas Audit - Khavid Normasyhuri; Fauzi Fauzi; Muhammad Suhaidi (Owner : Riset dan Jurnal Akuntansi, 2022)
This study tries to provide empirical evidence in order to see the factors that can affect audit quality, namely audit tenure and reputation of public accounting firms and see whether the audit committee can strengthen or even weaken in improving audit quality. The research sample is a manufacturing company listed on the Indonesia Stock Exchange from 2019-2021 with a purposive sampling technique. The number of observed samples was 96. The data analysis used was logistic regression and Moderate Regression Analysis. The statistical tool used is SPSS Version 21. The results of the study provide facts that audit tenure has no effect on improving audit quality. The reputation of the Public Accounting Firm has an influence on improving audit quality. The audit committee has not been able to moderate or weaken the relationship between audit period and audit quality improvement. The audit committee is able to moderate or strengthen the reputation of the Public Accounting Firm on improving audit quality.